Ponder: Realising enterprise viewpoint concepts - Lupu,E; Sloman,M; Dulay,N; Damianou,N (2000)
This paper introduces the Ponder language for specifying distributed object enterprise concepts. Ponder, is a declarative language, which permits the specification of policies in terms of obligations, permissions and prohibitions and provides the means for defining roles, relationships and their configurations in nested communities. Ponder provides a concrete representation of most of the concepts of the Enterprise Viewpoint. The design of the language incorporates lessons dl awn from sever al yeats of research on policy for security and distributed systems management as well as policy conflict analysis. The various language constructs are presented through a scenario for the operation, administration and maintenance of a mobile telecommunication network.